1975
DOI: 10.1111/j.1471-4159.1975.tb04354.x
|View full text |Cite
|
Sign up to set email alerts
|

The MECHANISM OF ACTION OF Β‐BUNGAROTOXIN

Abstract: —β‐Bungarotoxin, a presynaptically‐acting polypeptide neurotoxin, caused an efflux from synaptosomes of previously accumulated γ‐aminobutyric acid and 2‐deoxy‐d‐glucose. The toxin‐induced efflux of γ‐aminobutyric acid occurred by a Na+ ‐dependent process while that of 2‐deoxyglucose was Na+ ‐independent. These effects were also produced by treating synaptosomes with low molecular weight compounds, including fatty acids, that inhibit oxidative phosphorylation. After incubation with β‐bungarotoxin, synaptosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
2

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 43 publications
3
73
2
Order By: Relevance
“…Weak phospholipase A activity is also shown by the presynaptic neurotoxins, fl-bungarotoxin (Wernicke, Vanker & Howard, 1975), notexin (Halpert & Eaker, 1975) and taipoxin (Fohlman, Eaker, Karlsson & Thesleff, 1976). Although the role of catalytic activity in the neurotoxic action of notexin has been contested (Halpert, Eaker & Karlsson, 1976) it is strongly implicated in the action of G-bungarotoxin (Abe, Limbrick & Miledi, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Weak phospholipase A activity is also shown by the presynaptic neurotoxins, fl-bungarotoxin (Wernicke, Vanker & Howard, 1975), notexin (Halpert & Eaker, 1975) and taipoxin (Fohlman, Eaker, Karlsson & Thesleff, 1976). Although the role of catalytic activity in the neurotoxic action of notexin has been contested (Halpert, Eaker & Karlsson, 1976) it is strongly implicated in the action of G-bungarotoxin (Abe, Limbrick & Miledi, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Some snake toxins such as f3-bungarotoxin have also been found to cause depletion of synaptic vesicles at neuromuscular junctions (17), but it was found that nontransmitter substances were also released by this toxin (18). Because the nontransmitter, AIB, was not released by a-latrotoxin, it appears that a-latrotoxin is unique as a transmitter releasing agent.…”
Section: Methodsmentioning
confidence: 99%
“…wts. of 13 000 and 7500 which are linked by S-S bridges (Howard and Gundersen, 1980;Kelly and Brown, 1974;Wernicke et al, 1975). In common with other snake venom neurotoxins, the larger subunit carries a Ca2+-dependent phospholipase A2 activity (Strong et al, 1976 cross-linked membranes were subjected to SDS-polyacrylamide gel electrophoresis (SDS-PAGE) under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%